The Provision of Intensive Care and High Dependency Care in the Field. Issue 2 (1st June 2000) - Roberts, MJ; Salmon, JB; Sadler, PJ
Abstract : The Defence Medical Services aspire to deliver, whenever possible, United Kingdom peacetime standards of care to servicemen injured on active service. This level of medical support calls for the provision of adequate critical care to the severely ill or injured. This paper discusses the role of critical care in the field and how it may be most effectively deployed.